Jornalismo e crítica literária em Sérgio Augusto - Ventura, Mauro de Souza [UNESP]; Mateus, Felipe de Oliveira (My University, 2014)
The aim of this article is to analyze the journalistic elements existents in Sérgio Augusto’s literary criticism, in the column Prosa de Sábado, from the Supplement Sabático of the newspaper O Estado de S. Paulo. From the methodological point of view, it is guided by the studies of Pierre Bourdieu’s field theory. In addition, it discusses the relations between literary criticism and journalistic criticism based on Silviano Santiago and Flora Süssekind’s reflections, looking for establishing connections with the journalistic elements that inform Sergio Augusto’s literary criticism.

Este artigo tem por objetivo analisar os elementos jornalísticos existentes na crítica literária de Sérgio Augusto, na coluna Prosa de Sábado, do Suplemento Sabático, do jornal O Estado de S. Paulo. Do ponto de vista metodológico, orienta-se pelos estudos sobre a teoria dos campos de Pierre Bourdieu. Além disso, discorre sobre as relações entre crítica literária e crítica jornalística a partir das reflexões de Silviano Santiago e Flora Süssekind, buscando estabelecer conexões com os elementos jornalísticos que informam a crítica literária de Sérgio Augusto.
Journalism and literary criticism in Sérgio Augusto
Keywords: Literary criticism; Journalistic criticism; Sérgio Augusto; Cultural journalism; Supplement Sabático; Crítica literária; Crítica jornalística; Sérgio Augusto; Jornalismo cultural; Suplementos Literários